2015
DOI: 10.1007/s40328-015-0152-2
|View full text |Cite
|
Sign up to set email alerts
|

Computation of the changes in gravitational gradient components from GRACE observations and analytical model

Abstract: In this study the gravitational gradient changes caused by faulting on a finite rectangular plane buried in a homogenous half-space are computed using an analytical model which is a function of fault parameters. The sensitivity analysis of the analytical model with optional parameters revealed that the model is sensitive to the most of the fault parameters such as slip, depth, dip and is not sensitive to the strike. Also the results show that the model is sensitive to the length and the width of the fault. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…It appears better for shallow depth events (less than 15 km), occurring in a magnitude range of 5 to 7. This is consistent with a previous study of Fatolazadeh et al 43 who reported that increasing earthquake depth generates weakened gravity changes. It also explains why the GRACE-based approach did not capture clearly the severe earthquake of magnitude 7.9 and depth of 20 km, which occurred near the Sichuan-Gansu border in 15 th May 2008 in China (Fig.…”
Section: Error Analysissupporting
confidence: 94%
“…It appears better for shallow depth events (less than 15 km), occurring in a magnitude range of 5 to 7. This is consistent with a previous study of Fatolazadeh et al 43 who reported that increasing earthquake depth generates weakened gravity changes. It also explains why the GRACE-based approach did not capture clearly the severe earthquake of magnitude 7.9 and depth of 20 km, which occurred near the Sichuan-Gansu border in 15 th May 2008 in China (Fig.…”
Section: Error Analysissupporting
confidence: 94%
“…The gravity change due to earthquakes can be expressed by simplified but effective way, in which earthquake is modeled as dislocations on a rectangular plane in a homogeneous elastic half-space [Okubo 1991[Okubo , 1992. Fatolazadeh et. al [2015] developed this formulation in order to compute the gravity gradient changes resulting from earthquake [see also Wang et al, 2012c].…”
Section: Analytical Model Of Co-seismic Gravity Changementioning
confidence: 99%
“…[2016] Improved source parameter estimations for five undersea earthquakes from north component of GRACE gravity and gravity gradient change measurements. Recently, the formulation of Okubo's [1991Okubo's [ , 1992 model has been developed in order to compute the gravitational gradient changes resulting from earthquake [see Fatolazadeh et al, 2015;Wang et al, 2012c]. This analytical model was used to constrain the fault parameters of the 2010 Chile Earthquake using gravimetric observations [Fatolazadeh et al 2017].…”
Section: Introductionmentioning
confidence: 99%